Implications of the origem of bean lines in the magnitude of the interaction with environments - Silva, Camila Andrade; Abreu, Ângela de Fátima Barbosa; Ramalho, Magno Antonio Patto; Carneiro, José Eustáquio de Souza (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to verify the implications of the origens of bean lines in the magnitude of the interaction with environment, and the environmental factors, which contribute most to this interaction. Data from the value of cultivation and use trials of the biennia 2002/2003, 2005/2006, and 2007/2008, related to three cropping seasons in Lavras and Viçosa counties, MG, Brazil, were used. Lines from Universidade Federal de Lavras, Universidade Federal de Viçosa,  and Embrapa were evaluated. Grain yield data were subjected to the variance analysis for each environment and to joint analyses per biennium, for each local, and for both localities simultaneously. Coefficients of determination for each source of variation were determined, and stability analyses using ecovalence estimates were performed. Interactions with lines had small share in the total variation, in the three biennia. Despite the significance of genotype x local interactions for the total variation, its magnitud was not expressive. The location of the origin does not influence line stability when its environmental conditions are similar to those of the cultivation location, but influence the performance of lines when enviromental conditions differ greatly.
Keywords: Phaseolus vulgaris; ecovalence; stability; genotype x environment interaction